Solid-state electrolyte prepared by heterogeneous in-situ polymerization method and solid-state lithium / sodium battery containing solid-state electrolyte

Through gradient polymerization on the porous framework through heterogeneous in-situ polymerization, a solid electrolyte with a gradient structure was prepared, which solved the problems of low room temperature conductivity and interface impedance of the electrolyte, and achieved high stability and good cycling performance of the solid-state battery.

CN119695251AActive Publication Date: 2025-03-25JIANGSU UNIV

Patent Information

Application Number
CN202411856416.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In existing solid-state batteries, the electrolyte has low room temperature ion conductivity, narrow electrochemical windows and poor chemical/electrochemical stability, and the interface impedance between the solid electrolyte and the electrode is large, resulting in increased battery stability and commercialization difficulty.

Method used

The solid electrolyte is prepared by heterogeneous in-situ polymerization. By performing gradient polymerization on the porous framework, a gradient structure from solid to colloidal is formed, combining the advantages of solid and colloidal state, and improving the mechanical properties and interface binding ability of the electrolyte are improved.

Benefits of technology

The structural gradient changes of the electrolyte are achieved, the ionic conductivity, electrochemical stability and mechanical properties of solid-state batteries are improved, the growth and thermodynamic deformation of lithium dendrites are reduced, and the stability and cycling performance of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695251A_ABST
    Figure CN119695251A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid-state electrolytes, and particularly relates to a solid-state electrolyte prepared by a heterogeneous in-situ polymerization method and a solid-state lithium / sodium battery containing the solid-state electrolyte. The solid electrolyte prepared by the heterogeneous in-situ polymerization method has a gradient structure, specifically, the electrolyte on a framework is completely cured, the electrolyte near an electrode is in a gel state, and meanwhile, the solid electrolyte can be used for preparing a solid-state battery. The solid electrolyte with gradient structure change is prepared through heterogeneous in-situ polymerization, the structure gradient change of the electrolyte is realized, a gradient structure from a solid state to a colloidal state is formed, the dual advantages of the solid state and the colloidal state are combined, interface combination is facilitated, operation is simple, and structure regulation and control are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes, and more specifically relates to a solid electrolyte prepared by a heterogeneous in-situ polymerization method and a solid lithium or sodium battery containing the solid electrolyte. Background Art

[0002] Solid-state electrolytes are the core of solid-state batteries. Currently, solid-state batteries are classified mainly according to the type of solid-state electrolytes, including two major categories: ceramic (inorganic) solid-state electrolytes and polymer (organic) solid-state electrolytes. The former can be further subdivided into oxides, sulfides, nitrides, phosphides, etc. At present, the two categories that are more in-depth and have potential are mainly oxides and sulfides.

[0003] Judging from the current research results, polymer solid electrolytes have been applied first, but there are two fatal problems: high cost and low conductivity. The current mainstream polymer solid electrolytes are PEO, PVDF, PAN, etc. Polymer electrolytes have low conductivity at room temperature and low energy upper limit. After heating, the ionic conductivity is greatly improved, but it consumes energy and increases costs, which increases the difficulty of commercialization. Oxide solid electrolytes have good comprehensive performance. The important factor restricting their development is the large interface impedance between the electrolyte and the electrode, and the interface reaction causes the battery capacity to decay. Sulfide solid electrolytes have the highest conductivity and the highest research difficulty. How to maintain high stability is a major problem. Sulfide electrolytes have been favored by many companies due to their extremely high ionic conductivity and wide electrochemical stability window (above 5V), but the interface stability with lithium electrodes is poor. In contrast, organic / inorganic composite solid electrolytes have become the most promising technical solution for practical application because they combine the characteristics of inorganic electrolytes and polymer electrolytes.

[0004] Inorganic / organic composite solid electrolytes are usually formed by adding inorganic nanoparticles to polymer electrolytes. Currently, the polymer electrolytes that are studied more include polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polypropylene carbonate (PPC), etc. Pure polymer electrolytes generally have problems such as low room temperature ionic conductivity, narrow electrochemical window, and poor chemical / electrochemical stability. By adding inorganic nanoparticles, such as active fillers with ion conductivity, Li 7 La 3 Zr 2 O 12 (LLZO), Li 0.33 La 0.56 TiO 3 (LLTO), Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3(LATP), etc., or inert fillers without ionic conductivity, such as Al 2 O 3 、SiO 2 、TiO 2 、ZrO 2 The Lewis acidity of inorganic fillers can be used to improve the decomposition of lithium salts and reduce the crystallinity of polymers, thereby improving the ionic conductivity of composite electrolytes. It can also effectively improve the mechanical strength, electrochemical stability and thermal stability of polymer electrolytes. Using composite polymer electrolytes and regulating the ion transport path in the electrolyte by filler distribution is expected to provide a promising solution for promoting the practical application of solid electrolytes.

[0005] Although solid-state battery research has made great progress, in addition to solving the technical problems of the electrolyte itself, solid-state batteries also need to focus on solving the interface problems of solid electrolyte / electrode, including the interface contact impedance of the positive electrode / electrolyte, the interface compatibility of the negative electrode lithium / electrolyte, etc. The room temperature ionic conductivity of the solid electrolyte, the ion transport at the solid-solid interface of the electrode / electrolyte, and the cost and green process of the battery assembly process still need to be significantly broken through.

[0006] In-situ polymerization is an important method to solve the interface problem of solid-state batteries. Researchers have reported a variety of polymers and in-situ polymerization techniques, but the current in-situ polymerization is usually homogeneous polymerization, that is, the electrolyte slurry mixed with initiator is directly poured into the battery, and solidified by thermal polymerization, photopolymerization or catalyst-induced polymerization. As a result, the internal spatial structure of the battery is single, either completely solidified with poor interface flexibility, or gelled and incompletely solidified. It can be seen that complete solidification or complete gelation is not conducive to the stability of solid-state batteries. The actual demand is that the electrolyte must be solidified to a certain strength to inhibit the growth of lithium dendrites and thermodynamic deformation, while maintaining the flexible combination of the electrode / electrolyte interface so that the battery will not experience interface separation due to volume changes in the electrodes during charging and discharging. Summary of the invention

[0007] The purpose of the present invention is to provide a solid electrolyte prepared by a heterogeneous in-situ polymerization method and a solid-state lithium or sodium battery containing the solid electrolyte. The gradient polymerization structure, i.e., heterogeneous in-situ polymerization, solves the practical needs of structural gradient change of the electrolyte and simplified operation, realizes structural regulation (from an ordinary homogeneous structure to a gradient structure), and is easy to form a gradient structure that takes both rigidity and flexibility into consideration from a solid state to a colloidal state. The dual advantages of the solid state and the colloidal state are combined. The good mechanical properties of the solid state are conducive to the suppression of lithium dendrites, and the gel state is conducive to interface bonding and buffering the stress concentration caused by the volume change of the electrode during charge and discharge, thereby solving the problems existing in the above-mentioned prior art.

[0008] To achieve the above object, the present invention provides the following solutions:

[0009] One of the technical solutions of the present invention is to provide a solid electrolyte prepared by a heterogeneous in-situ polymerization method, comprising a porous skeleton and an electrolyte with a gradient structure supported on the porous skeleton;

[0010] The electrolyte is completely solidified on the porous skeleton and is in a gel state near the electrode.

[0011] Furthermore, the electrolyte includes a metal salt and a monomer.

[0012] The second technical solution of the present invention is to provide a method for preparing the above-mentioned solid electrolyte, comprising the following steps:

[0013] preparing an initiator, a binder and a filler into a slurry;

[0014] The slurry is coated on a porous skeleton, and after drying, an electrolyte solution is poured, and the solid electrolyte is obtained by gradient polymerization;

[0015] The electrolyte solution includes a metal salt and a polymer monomer.

[0016] Furthermore, the concentration of the initiator in the slurry is 1 to 5 wt.%.

[0017] Furthermore, the concentration of the binder in the slurry is 1 to 5 wt.%.

[0018] Furthermore, the concentration of the filler in the slurry is 10 to 50 wt.%.

[0019] Furthermore, the initiator comprises aluminum trifluoromethanesulfonate (Al(OTf) 3 ), stannous octoate (Sn(Oct) 2 ), lithium hexafluorophosphate (LiPF 6 ) and at least one of azobisisobutyronitrile (AIBN).

[0020] Furthermore, the binder includes at least one of non-ionic block copolymer F127, water-based binder LA123, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and polypropylene carbonate (PPC).

[0021] Furthermore, the filler includes YSZ, LLZO, LAGP, Li-β″-Al 2 O 3 , LLTO, NLZO and Na-β″-Al 2 O 3 At least one of .

[0022] The introduction of fillers can improve the uniform distribution of initiators and improve the ionic conductivity, thermal and mechanical properties of polymer electrolytes by compounding with polymers.

[0023] Optionally, when preparing the slurry, the solvent is deionized water, DMF, NMP, ethanol or acetone.

[0024] Furthermore, the porous skeleton has a porosity greater than 50%.

[0025] Optionally, the porous skeleton is a dry PE membrane, an electrospun PI fiber membrane, a PET fiber membrane, a PVDF fiber membrane, a glass fiber membrane or a cellulose membrane.

[0026] Furthermore, the metal salt includes LiTFSI, LiFSI, LiClO 3 、LiBOB、NaTFSI、NaPF 6 、NaClO 3 , NaFSI and NaBOB.

[0027] Furthermore, the polymer monomer includes at least one of 1,3-dioxolane (DOL), polyethylene glycol methyl ether acrylate (PEGMEA), methyl methacrylate (MMA), polyethylene glycol diglycidyl ether (PEGDE), succinonitrile (SN), and triglycidyl isocyanurate (TGIC).

[0028] The polymer obtained by self-polymerization or combined polymerization of the above polymer monomers includes but is not limited to one of PDOL, PEGMEA-PMMA, PDOL-PMMA, PEGDE-PMMA, PEGMEA-PMMA-SN, and PDOL-TGIC.

[0029] Furthermore, the gradient polymerization is achieved by autocatalysis or thermal initiation, and the time is 30 minutes to 24 hours.

[0030] Optionally, the temperature of the autocatalysis is room temperature; the temperature of the thermal initiation is 40-60°C.

[0031] The present invention controls the position of the initiator. The polymerization is fast and the polymerization degree is high at the place where the initiator is concentrated (on the skeleton), while the polymerization degree is low outside the skeleton. The farther away from the skeleton, the lower the polymerization degree.

[0032] The third technical solution of the present invention is to provide an application of a solid electrolyte prepared by the above-mentioned heterogeneous in-situ polymerization method in a solid-state battery.

[0033] Optionally, the solid-state battery is a solid-state lithium battery or a solid-state sodium battery.

[0034] Technical solution four of the present invention: provides a solid-state battery, which includes a solid electrolyte prepared by the above-mentioned heterogeneous in-situ polymerization method.

[0035] Furthermore, the preparation steps of the solid-state battery include:

[0036] S1, preparing an initiator, a binder and a filler into a slurry;

[0037] The concentration of the initiator in the slurry is 1-5wt.%; the concentration of the binder in the slurry is 1-5wt.%; the concentration of the filler in the slurry is 10-50wt.%; the solvent of the slurry is deionized water, DMF, NMP, ethanol or acetone;

[0038] S2, using a doctor blade method to evenly coat the slurry on the surface of a porous skeleton with a porosity greater than 50%, with a coating thickness of 5 to 200 μm, leaving it to stand for 10 to 20 minutes (for the porous skeleton to fully adsorb the slurry), and obtaining a diaphragm after drying;

[0039] Wherein, the porous skeleton is a dry PE membrane, an electrospun PI fiber membrane, a PET fiber membrane, a PVDF fiber membrane, a glass fiber membrane or a cellulose membrane;

[0040] S3, placing the separator in a battery, forming a battery core with the electrode, pouring the electrolyte solution into the battery, filling it up, sealing it, and curing it at room temperature or by heating at 40 to 60° C. for 30 min to 24 h to obtain a solid-state battery;

[0041] The electrolyte solution contains metal salt and polymer monomer.

[0042] Optionally, the initiator comprises aluminum trifluoromethanesulfonate (Al(OTf) 3 ), stannous octoate (Sn(Oct) 2 ), lithium hexafluorophosphate (LiPF 6 ) and at least one of azobisisobutyronitrile (AIBN).

[0043] Optionally, the binder includes at least one of non-ionic block copolymer F127, aqueous binder LA123, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and polypropylene carbonate (PPC).

[0044] Optionally, the filler includes YSZ, LLZO, LAGP, Li-β″-Al 2 O 3 , LLTO, NLZO and Na-β″-Al 2 O 3 At least one of .

[0045] Optionally, the metal salt includes LiTFSI, LiFSI, LiClO 3 、LiBOB、NaTFSI、NaPF 6 、NaClO 3 , NaFSI and NaBOB.

[0046] Optionally, the polymer monomer includes at least one of 1,3-dioxolane (DOL), polyethylene glycol methyl ether acrylate (PEGMEA), methyl methacrylate (MMA), polyethylene glycol diglycidyl ether (PEGDE), succinonitrile (SN), and triglycidyl isocyanurate (TGIC).

[0047] The polymer obtained by self-polymerization or combined polymerization of the above polymer monomers includes but is not limited to one of PDOL, PEGMEA-PMMA, PDOL-PMMA, PEGDE-PMMA, PEGMEA-PMMA-SN, and PDOL-TGIC.

[0048] Optionally, the electrode includes a positive electrode and a negative electrode; wherein the positive electrode includes lithium iron phosphate, sodium vanadium phosphate, a ternary lithium positive electrode or a ternary sodium; and the negative electrode includes metallic lithium, metallic sodium, graphite or hard carbon.

[0049] The present invention discloses the following technical effects:

[0050] The present invention prepares a solid electrolyte with a gradient structural change through heterogeneous in-situ polymerization, realizes the structural gradient change of the electrolyte, forms a gradient structure from solid to colloidal, combines the dual advantages of solid and colloidal, is conducive to interface bonding, is simple to operate, and is convenient for structural regulation.

[0051] The initiator is applied to the skeleton in advance, and then the electrolyte components are poured. The skeleton has a high concentration of initiator, which can make the electrolyte quickly polymerize into a solid. There is no initiator outside the skeleton, and the polymerization can only be initiated by the partially dissolved initiator on the skeleton. The degree of polymerization is not as high as that on the skeleton because of the small amount of initiator. The farther away from the skeleton, the lower the degree of polymerization, thus achieving a gradient structure from solid to colloidal, or even semi-solid. Therefore, the location of the initiator is controlled, and the degree of polymerization is regulated by the concentration of the initiator in different areas of the electrolyte.

[0052] The filler is added to better evenly distribute the initiator on the skeleton, and secondly to improve the ionic conductivity of the electrolyte. It can also be used as a coating to improve its mechanical and thermal properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0054] Figure 1 This is the cycle performance of the solid-state battery in Example 1.

[0055] Figure 2 This is the rate performance of the solid-state battery in Example 1.

[0056] Figure 3 It is the potential window of the solid-state battery in Example 1.

[0057] Figure 4 This is a SEM image of the polyethylene skeleton coated with initiator and filler in Example 1.

[0058] Figure 5 This is a SEM image of the cross section of the solid electrolyte after polymerization in Example 1.

[0059] Figure 6 This is the SEM image of the PI fiber skeleton coated with initiator and filler in Example 2.

[0060] Figure 7 This is a SEM image of the cross section of the solid electrolyte after polymerization in Example 2.

[0061] Figure 8 Schematic diagram of the preparation of solid-state electrolytes by homogeneous in situ polymerization.

[0062] Fig. 9 Schematic diagram of the preparation of solid-state electrolytes by heterogeneous in situ polymerization. DETAILED DESCRIPTION

[0063] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0064] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0065] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0066] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0067] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0068] The raw materials and reagents used in the specific embodiments of the present invention are all commercially available products; unless otherwise specified, the room temperature and normal temperature referred to are both 20-30°C.

[0069] Example 1

[0070] Preparation of solid-state batteries:

[0071] S1, 0.15g Al(OTf) 3 0.03 g PVDF was dissolved in 3 g DMF, 0.3 g YSZ nanoparticles were added, degassed for 3 min using a degasser, and magnetically stirred for 4-5 h to obtain a slurry;

[0072] S2, drip the slurry evenly on the glass plate, scrape it evenly with a scraper with a gap of 150 μm, then spread the polyethylene skeleton (porosity greater than 50%) evenly on the scraped slurry, then drip the slurry on the upper layer, scrape it evenly with a scraper with a gap of 200 μm, put it on a flat place to dry at room temperature for 10 to 20 minutes, then dry it in a blast drying oven (60°C) until there is no liquid on the surface, hang it at 80°C for blast drying for 8 hours, and vacuum dry it for 12 hours to obtain a diaphragm, and store it in an argon glove box for later use;

[0073] S3, 0.287 g LiTFSI and 1 g DOL were mixed and stirred for 10 min until fully dissolved to obtain a uniform electrolyte solution;

[0074] S4. Use 2032 button battery as assembly shell, lithium iron phosphate as positive electrode and metal lithium sheet as negative electrode, place the above-prepared diaphragm (polyethylene skeleton loaded with initiator) between the positive and negative electrodes, and drip 40μL electrolyte solution on both sides respectively. After standing for 20 minutes, press the button with a pressure of 50Mpa. After curing at room temperature for 12 hours, a solid-state battery is obtained.

[0075] The electrochemical performance of the solid-state battery prepared in Example 1 was tested, and the results were as follows: Figures 1 to 3 shown.

[0076] Figure 1 is the cycle performance of the solid-state battery in Example 1; Figure 2 is the rate performance of the solid-state battery in Example 1; Figure 3 is the potential window of the solid-state battery in Example 1. Figure 1 to Figure 3 It can be seen that the ionic conductivity of the solid-state battery prepared in Example 1 is 2×10 -4 S / cm, the potential window can reach 5.2V, the rate performance is good, it can reach more than 120mAh / g at 1C, and it can be stably cycled for 500 weeks at 0.5C with a capacity retention of 85%.

[0077] Figure 4 This is the SEM image of the polyethylene skeleton (diaphragm) covered with initiator and filler in Example 1.

[0078] Figure 5 This is a SEM image of the cross section of the solid electrolyte after polymerization in Example 1.

[0079] analyze Figure 4-5 It can be found that the electrolyte on the skeleton has been completely solidified into a solid state, while the surface (i.e., the interface in contact with the electrode) maintains an obvious colloidal state. This structure is a good solution to the interface problem of solid-state batteries.

[0080] Example 2

[0081] Preparation of solid-state batteries:

[0082] S1. Dissolve 0.5 g LLZO filler, 0.1 g AIBN initiator, and 0.03 g F127 binder in 3 g anhydrous ethanol, degas with a degasser for 3 min, and stir with a magnetic stirrer for 4-5 h to obtain a slurry;

[0083] S2. The slurry was evenly coated on the PI fiber skeleton (porosity greater than 50%) by a doctor blade method with a thickness of 200 μm, and allowed to stand for 10 min for full adsorption by the skeleton, and then dried in an oven (80° C.) for 12 h to obtain a diaphragm, which was stored in an argon glove box for later use;

[0084] S3, mix LiTFSI lithium salt and PEGMEA+MMA+SN (mass ratio 1:9:7), stir for 10 min until fully dissolved, and obtain a uniform electrolyte solution;

[0085] S4. Use 2032 button battery as assembly shell, lithium iron phosphate as positive electrode and metal lithium sheet as negative electrode, place the above-prepared diaphragm (PI fiber skeleton loaded with initiator) between the positive and negative electrodes, and drip 40μL electrolyte solution on both sides respectively. After standing for 20 minutes, press the button with a pressure of 50Mpa and cure at 60℃ for 30 minutes to obtain a solid-state battery.

[0086] The electrochemical performance of the solid-state battery obtained in Example 2 was tested, wherein the ionic conductivity of the electrolyte was 3.7×10 -4 S / cm, the potential window reaches 5.0V, the rate performance is good, it can reach more than 131mAh / g at 1C, and it can be stably cycled for 500 weeks at 0.5C, with the capacity retention of 87%.

[0087] Figure 6 This is the SEM image of the PI fiber skeleton (diaphragm) coated with initiator and filler in Example 2.

[0088] Figure 7 This is a SEM image of the cross section of the solid electrolyte after polymerization in Example 2.

[0089] Example 3

[0090] Preparation of solid-state batteries:

[0091] S1, 0.5g Li-β″-Al 2 O 3 Filler, 0.1g Sn(Oct) 2 The initiator and 0.03 g of PVDF binder were mixed and dissolved in 3 g of N,N-dimethylformamide, degassed for 3 min using a degasser, and magnetically stirred for 4 to 5 h to obtain a slurry;

[0092] S2. The slurry was evenly coated on a PET fiber skeleton (porosity greater than 50%) by a doctor blade method with a thickness of 200 μm, and allowed to stand for 10 min for full adsorption on the skeleton, and then dried in an oven (100° C.) for 12 h to obtain a diaphragm, which was stored in an argon glove box for later use;

[0093] S3, LiClO 3 The lithium salt and DOL+TGIC (mass ratio 10:1) were mixed and stirred for 10 min until fully dissolved to obtain a uniform electrolyte solution;

[0094] S4. Use 2032 button battery as assembly shell, ternary NCM622 as positive electrode and metal lithium sheet as negative electrode, place the above-prepared diaphragm (PET fiber skeleton loaded with initiator) between the positive and negative electrodes, and drip 40μL electrolyte solution on both sides respectively. After standing for 20 minutes, press the battery with a pressure of 50Mpa and cure it at 60℃ for 60 minutes to obtain a solid-state battery.

[0095] The electrochemical performance of the solid-state battery obtained in Example 3 was tested, wherein the ionic conductivity of the electrolyte was 5.3×10 -4 S / cm, the potential window reaches 5.2V, the rate performance is good, it can reach more than 161mAh / g at 1C, and it can be stably cycled for 500 weeks at 0.5C, with the capacity retained at 80%.

[0096] Example 4

[0097] Preparation of solid-state batteries:

[0098] S1, 0.5g Na-β″-Al 2 O 3 The filler, 0.1 g AIBN initiator, and 0.03 g F127 binder were mixed and dissolved in 3 g NMP, degassed for 3 min using a degasser, and stirred magnetically for 4 to 5 h to obtain a slurry;

[0099] S2. The slurry was evenly coated on the PVDF fiber skeleton (porosity greater than 50%) by a doctor blade method with a thickness of 200 μm, and allowed to stand for 10 min for full adsorption by the skeleton, and then dried in an oven (80° C.) for 12 h to obtain a diaphragm, which was stored in an argon glove box for later use;

[0100] S3, mixing NaTFSI sodium salt and PEGMEA-MMA (mass ratio 2:9), stirring for 10 min until fully dissolved, to obtain a uniform electrolyte solution;

[0101] S4. Use 2032 button battery as assembly shell, sodium vanadium phosphate as positive electrode and metallic sodium as negative electrode, place the above-prepared diaphragm (PVDF fiber skeleton loaded with initiator) between the positive and negative electrodes, and drip 40μL electrolyte solution on both sides respectively. After standing for 20 minutes, press the button with a pressure of 50Mpa and cure at 60℃ for 30 minutes to obtain a solid-state battery.

[0102] The electrochemical performance of the solid-state battery obtained in Example 4 was tested, wherein the ionic conductivity of the electrolyte was 3.1×10 -4 S / cm, the potential window reaches 4.8V, the rate performance is good, it can reach more than 101mAh / g at 1C, and it can be stably cycled for 500 weeks at 0.5C with a capacity retention of 80%.

[0103] Comparative Example 1

[0104] Preparation of homogeneous polymerization solid-state batteries:

[0105] S1. Mix 0.5 g LLZO filler, 0.1 g AIBN initiator, 0.5 g LiTFSI lithium salt and 5 g PEGMEA+MMA+SN (mass ratio 1:9:7), and stir for 10 min until fully dissolved to obtain a uniform electrolyte solution;

[0106] S2. Use 2032 button battery as assembly shell, lithium iron phosphate as positive electrode and metal lithium sheet as negative electrode, place PI fiber skeleton between positive and negative electrodes, and drip 40μL electrolyte solution on both sides respectively. After standing for 20 minutes, press the button with a pressure of 50Mpa and cure at 60℃ for 30 minutes to obtain a solid-state battery.

[0107] The electrochemical performance of the solid-state battery obtained in Comparative Example 1 was tested, wherein the ionic conductivity of the electrolyte was 1.8×10 -4 S / cm, the potential window reaches 4.4V, the rate performance is good, it can reach more than 117mAh / g at 1C, and it can be stably cycled for 200 weeks at 0.5C, with the capacity retained at 79%.

[0108] Figure 8 Schematic diagram of the preparation of solid-state electrolytes by homogeneous in situ polymerization.

[0109] Fig. 9 Schematic diagram of the preparation of solid-state electrolytes by heterogeneous in situ polymerization.

[0110] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0111] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A solid electrolyte prepared by a heterogeneous in-situ polymerization method, characterized in that: It comprises a porous skeleton and an electrolyte with a gradient structure supported on the porous skeleton; The electrolyte is completely solidified on the porous skeleton and is in a gel state near the electrode.

2. A method for preparing a solid electrolyte according to claim 1, characterized in that the steps include: preparing an initiator, a binder and a filler into a slurry; The slurry is coated on a porous skeleton, and after drying, an electrolyte solution is poured, and the solid electrolyte is obtained by gradient polymerization; The electrolyte solution includes a metal salt and a polymer monomer.

3. The preparation method according to claim 2, characterized in that: The concentration of the initiator in the slurry is 1 to 5 wt.%; and / or, The concentration of the binder in the slurry is 1 to 5 wt.%; and / or, The concentration of the filler in the slurry is 10-50 wt.%.

4. The preparation method according to claim 2, characterized in that: The initiator comprises at least one of aluminum trifluoromethanesulfonate, stannous octoate, lithium hexafluorophosphate and azobisisobutyronitrile; and / or, The binder comprises at least one of nonionic block copolymer F127, aqueous binder LA123, polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer and polypropylene carbonate; and / or, The filler comprises at least one of YSZ, LLZO, LAGP, Li-β″-Al2O3, LLTO, NLZO and Na-β″-Al2O3; and / or, The porous skeleton has a porosity greater than 50%.

5. The preparation method according to claim 4, characterized in that: The porous skeleton is a dry PE membrane, an electrospun PI fiber membrane, a PET fiber membrane, a PVDF fiber membrane, a glass fiber membrane or a cellulose membrane.

6. The preparation method according to claim 2, characterized in that: The metal salt comprises at least one of LiTFSI, LiFSI, LiClO3, LiBOB, NaTFSI, NaPF6, NaClO3, NaFSI and NaBOB; and / or, The polymer monomer includes at least one of 1,3-dioxolane, polyethylene glycol methyl ether acrylate, methyl methacrylate, polyethylene glycol diglycidyl ether, succinonitrile and triglycidyl isocyanurate.

7. The preparation method according to claim 2, characterized in that: The gradient polymerization is achieved by autocatalysis or thermal initiation, and the time is 30 minutes to 24 hours.

8. The preparation method according to claim 7, characterized in that: The temperature of the autocatalysis is room temperature; and / or, The thermal initiation temperature is 40-60°C.

9. Use of the solid electrolyte prepared by the heterogeneous in-situ polymerization method according to claim 1 in a solid-state battery.

10. A solid-state battery, characterized in that: The solid-state battery comprises a solid electrolyte prepared by the heterogeneous in-situ polymerization method according to claim 1.

Citation Information

Patent Citations

  • Solid composite electrolyte membrane, manufacturing method thereof and polymer secondary battery

    CN111864258A

  • Gel lithium ion battery preparation method and prepared gel lithium ion battery

    CN114284554A

  • Preparation method of composite solid electrolyte with gradient structure

    CN115799626A

  • Composite solid electrolyte as well as preparation method and application thereof

    CN118173864A

  • In-situ solid-state battery and preparation method thereof

    CN119029361A

Cited By

  • Preparation method of in-situ polymerization semi-solid electrolyte with gradient concentration distribution

    CN121460700A